Nutritional status and dietary intake of urban residents in Gondar, Northwest Ethiopia - Amare Bemnet; Moges Beyene; Moges Feleke; Fantahun Bereket; Admassu Mengesha; Mulu Andargachew; Kassu Afework (BMC, 2012)
Abstract Background There is paucity of data on the dietary intake and nutritional status of urban Ethiopians which necessitates comprehensive nutritional assessments. Therefore, the present study was aimed at evaluating the dietary intake and nutritional status of urban residents in Northwest Ethiopia. Methods This cross-sectional community based nutrition survey was conducted by involving 356 participants (71.3% female and 28.7% male with mean age of 37.3 years). Subjects were selected by random sampling. Socio demographic data was collected by questionnaire. Height, weight, hip circumference and waist circumference were measured following standard procedures. Dietary intake was assessed by a food frequency questionnaire and 24-h dietary recall. The recommended dietary allowance was taken as the cut-off point for the assessment of the adequacy of individual nutrient intake. Results Undernourished, overweight and obese subjects composed 12.9%, 21.3% and 5.9% of the participants, respectively. Men were taller, heavier and had higher waist to hip ratio compared to women (P < 0.05). Fish, fruits and vegetables were consumed less frequently or never at all by a large proportion of the subjects. Oil and butter were eaten daily by most of the participants. Mean energy intakes fell below the estimated energy requirements in women (1929 vs 2031 kcal/day, P = 0.05) while it was significantly higher in men participants (3001 vs 2510 kcal/day, P = 0.007). Protein intake was inadequate (<0.8 g/kg/day) in 11.2% of the participants whereas only 2.8% reported carbohydrate intake below the recommended dietary allowances (130 g/day). Inadequate intakes of calcium, retinol, thiamin, riboflavin, niacin and ascorbic acid were seen in 90.4%, 100%, 73%, 92.4%, 86.2% and 95.5% of the participants. Conclusions The overall risk of nutritional inadequacy among the study participants was high along with their poor dietary intake. Hence, more stress should be made on planning and implementing nutritional programmes in urban settings aimed at preventing or correcting micronutrient and some macronutrient deficiencies which may be useful in preventing nutrition related diseases in life.